Revalorization problems of the down-town areas on the example of Zielona Góra = Z problemów rewaloryzacji terenów śródmiejskich na przykładzie Zielonej Góry - Kononowicz, Wanda; Sukienniczak, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the considerations presented in the article is to determine the developmental directions of the inner urban areas respecting and honouring the cultural heritage of Zielona Gora city. The formation of useful physical form of the urban lifestyle environment is particularly important in the process of urban regeneration.
Keywords: revitalisation; downtown area; urban policy; Zielona Góra; rewitalizacja; tereny śródmiejskie; polityka miejska